Gender and clinical trials: is the Regulation n. 536/2914 (EU) a missed opportunity? (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
This paper aims at discussing the Regulation n. 536/2914 (EU) under a gendered perspective. In the first part the article will discuss the importance of the gender-specific medicine approach and its latest applications and implications in the field of clinical trials. After this, the relevant norms in the Regulation will be highlighted and discussed. A critique will be provided, after having analyzed some relevant national experiences (USA, Canada, Italy, in particular). In the last paragraph some suggestions for further implementation will be discussed.
Keywords: Gender; clinical trials; EU Regulation 536/2014; health inequalities; gender-specific medicine